Infant feeding, solid foods and hospitalisation in the first 8 months after birth. Issue 2 (1st October 2008) - Quigley, M A; Kelly, Y J; Sacker, A
Abstract : Most infants in the UK start solids before the recommended age of 6 months. We assessed the independent effects of solids and breast feeding on the risk of hospitalisation for infection in term, singleton infants in the Millennium Cohort Study (n = 15 980). For both diarrhoea and lower respiratory tract infection (LRTI), the monthly risk of hospitalisation was significantly lower in those receiving breast milk compared with those receiving formula. The monthly risk of hospitalisation was not significantly higher in those who had received solids compared with those not on solids (for diarrhoea, adjusted odds ratio 1.39, 95% CI 0.75 to 2.59; for LRTI, adjusted odds ratio 1.14, 95% CI 0.76 to 1.70), and the risk did not vary significantly according to the age of starting solids.